What Are the Economic Costs of Gender Gaps in Ethiopia? - Buehren, Niklas; Gonzalez, Paula; Copley, Amy (World Bank, Washington, DC, 2019)
Despite Ethiopia’s remarkable economic progress over the past decade, gender gaps in key economic activities - agriculture, entrepreneurship, and wage employment - indicate that challenges remain to realizing the full potential of women’s economic empowerment. Differences in simple averages between men and women show that women lag men by 36 percent in agricultural productivity, by 79 percent in business sales, and by 44 percent in hourly wages. This brief examines the costs of these gender gaps and estimates the potential gains from closing them.